Family background and classroom belonging among adolescent students in Finland - Hautala Helena; Lehti Hanna; Kallio Johanna (Springer, 2025)
We study whether a family’s economic situation and parental educational level are
associated with classroom belonging among students in comprehensive secondary,
upper secondary general and upper secondary vocational education in Finland. We
also study whether there are educational-level differences in this possible association.
We use survey data from the Finnish School Health Promotion study from 2017
(N = 114,528). We conduct random effect linear probability models with schools as
the second-level grouping variable. The results show that family’s low economic
situation predicts a higher probability of lack of sense of classroom belonging in
Finland, despite the country having one of the world’s most equal educational systems
and comparably low economic inequality. Neither mother’s nor father’s educational
level has any association. A family’s low economic situation seems to predict
the lack of a sense of belonging most strongly in comprehensive secondary education
and most weakly in upper secondary vocational education. Our results slightly
support the proposed significance of context-specific hierarchies in determining the
association between economic resources and sense of belonging. A family having
a poor economic situation is not reflected in the sense of classroom belonging as
strongly in schools where students have a low average economic situation compared
to those where students have a high average economic situation. We suggest measures,
in addition to alleviating economic inequalities, to support the sense of school
belonging, especially for low-income students.